Customer Shopping Behavior among Modern Retail Formats:A Study of Delhi & NCR - Pathak, S. V.; Tripathi, Aditya P. (Indian Journal of Marketing, 2009)
The Indian retail sector is going through a transformation and this emerging market is witnessing a significant change in its growth and investment pattern. Both existing and new players are experimenting with new retail formats. Currently two popular formats hypermarkets and supermarkets are growing at a rapid pace. Apart from the brick-mortar formats, brick-click and click-click formats are also increasingly functional on the Indian retail landscape. Consumer dynamics in India is also changing and the retailers need to take note of this and formulate their strategies and tactics to deliver the exact expected value to the customer. In the backdrop of all these developments the present paper makes an attempt to: To find out the factors that affect the buyers’ decision among the modern retail formats, and Evaluates he comparative strength of these factors in buying decision process. It Reveals the Consumer Shopping Behavior) among the Modern Retail Formats with special reference to Delhi & NCR. The empirical data has been collected with the help of Primary as well as secondary resources. The Primary research was conducted at Different Malls of Delhi & NCR.